2021
DOI: 10.1186/s40658-021-00418-y
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis of 11C-methionine PET in patients with newly diagnosed glioma

Abstract: Background The present study tested the possible utility of fractal analysis from l-[methyl-11C]-methionine (MET) uptake in patients with newly diagnosed gliomas for differentiating glioma, especially in relation to isocitrate dehydrogenase 1 (IDH1) mutation status, and as compared with the conventional standardized uptake value (SUV) parameters. Methods Investigations of MET PET/CT were performed retrospectively in 47 patients with newly diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Furthermore, they found that the FD measure was able to classify LGG and HGG patients with 81% sensitivity and 89% specificity and concluded that FD can be a novel imaging biomarker for glioma. Functional 11C-methionine PET imaging was performed in Maeda et al (2021 , 11) that employed a fractal dimension approach in newly diagnosed glioma patients. They also observed a significant difference ( p < 0.001) in FD values between LGG and HGG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they found that the FD measure was able to classify LGG and HGG patients with 81% sensitivity and 89% specificity and concluded that FD can be a novel imaging biomarker for glioma. Functional 11C-methionine PET imaging was performed in Maeda et al (2021 , 11) that employed a fractal dimension approach in newly diagnosed glioma patients. They also observed a significant difference ( p < 0.001) in FD values between LGG and HGG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fractal dimension (FD) seems to be a measure of the fractal properties that describe the space-filling properties of networks, including biological systems. FD has been applied to histopathological studies to determine the complexity of certain tissue components 21 – 24 . Biscetti et al 25 measured FD and other parameters of superficial capillary plexus (SCP), intermediate capillary plexus (ICP), deep capillary plexus (DCP), and choriocapillaris of subjects with mild cognitive impairment (MCI) due to AD and cognitively healthy controls (CN).…”
Section: Related Workmentioning
confidence: 99%
“…The greater the overall accumulation of 11 C-MET, the shorter the patient survival. Maeda et al showed that fractal analysis of 11 C-MET PET in patients with newly diagnosed GBM could differentiate low-grade glioma and glioblastoma as well as indicated the IDH1 mutation status [39]. The fractal dimension measures the pattern of the radioactivity distribution in the region of interest.…”
Section: The Accumulation Of 11 C-methionine By Glioblastoma Tumor Ce...mentioning
confidence: 99%